Pengaruh Pembangunan Manusia terhadap Kinerja Ekonomi Regional di Kota Pematangsiantar - Rizky Febrian Saragih; Anugrah Ramanda Lubis; Muhammad Sendi; Tryana Ramadhany Batubara; Juliana Nasution (Universitas Muhammadiyah Enrekang, 2022)
This analysis is meaningful in order to know the effect of people development on regional economics performance in Pematangsiantar City. The analytical method used is a qualitative method in the form of descriptive, namely by using a method where the author analyzes the data obtained and describes through the events related to the problem. The results of this study show that there has been a very significant decline in the Development of Economic Growth in the City of Pematangsiantar at 2015-2020. Where that the degree of fiscal decentralization has an impact on economic growth. This is the impact of the degree of fiscal decentralization on economic development stating that the degree of fiscal decentralization has a negative effect on economic growth.